Penilaian Sistem Proteksi Kebakaran Pada Gedung Telkom Sentral Telepon Pattimura Menggunakan PD-T-11-2005-C - Sarif, Sarif; A Sangadji, Fauzan; G Buyang , Christy (Jurnal Basement : Jurnal Teknik Sipil, 2025)
Fire is a problem that cannot be separated from humans, and the losses caused by the dangers of fire are not only in the form of building damage, but also losses that involve human lives. The potential for fire in Ambon City is quite high in buildings that use electronic devices, one of which is the Telkom Central Telephone Pattimura building. This building functions as a strategic node in the national telecommunications infrastructure network. On February 5, 2019, the Telkom Central Telephone Pattimura building experienced a fire caused by a short circuit so that the fire quickly burned the rooms full of Telkomsel network cables. So the Telkom building needs to ensure the safety of the building again from the dangers of fire by using technical guidelines, namely Pd-T-11-2005-C. The purpose of this study is to identify the completeness of K3 facilities and assess the reliability of the Telkom Central Telephone Pattimura building. This type of research is quantitative descriptive conducted at the Central Telephone Pattimura building for 1 month by conducting observations and document reviews. All observation data has been collected and then analyzed to obtain the building safety system reliability value (NKSKB). The results of the research at the Telkom Central Telephone Pattimura building produced a Building Safety System Reliability Value (NKSKB) of 34.51% which means the level of readiness of K3 facilities in this research building is categorized as less (K).